Software engineering : - Jawadekar, Waman S. (Tata McGraw-Hill Pub., 2004)
The book has been written according to the syllabus prescribed by the Directorate General of Employment and Training for the Craftsman Training Scheme and the Apprenticeship Training Scheme for the Electrical Trades (Electrician, Wireman and Lineman). The first volume covers what should be taught in the first year. The language is very simple and the concepts are explained with the help of clear illustrations. The theory is supported by practical applications of the concepts. A number of solved examples have been provided. At each chapter end is a set of unsolved numerical problems and review questions. Answers to these have been provided. These review questions are taken from the examination papers of the National Council for Vocational trades and from the All India Skill Competitions. This book will help trainees and apprentices prepare themselves for the final examination and for the job interviews.